An insight on parents and youth perception on aspects contributing to child marriage in Sabah / Norsabariane Ajat, Muhammad Yudrey Yusuf and Jennifah Nordin - Ajat, Norsabariane; Yusuf, Muhammad Yudrey; Nordin, Jennifah (2021)
Child marriage is a very common issue being discussed in many countries around the earth for so long and has become a vital topic till now. Convention on the right of the child (CRC) and Child Act 2001 defined "child" as any person under the age of 18. Both laws recognise on importance of the human rights of children. They must be protected from any violence, injury, abuse, neglect, mistreatment, and exploitation. Child marriage is referred to any individual who gets into a marriage life when at least one or both partners are below eighteen years old. This kind of marriage has always been associated with forced marriage and social crime since children are not allowed to give full consent and the marriage exposed them to various social issues such as domestic violence and unwanted pregnancy (United Nations Human Rights, n.d). In March 2021 it was reported by UNICEF Executive Director Henriett fore that the COVID-19 pandemic is expected to put more than 10 million girls at risk of child marriage due to educational institutions are closed, limited social interaction, and the rise of poverty. This problem caught the attention of the United Nations Sustainable Development Goals and a global serious attempt called to end this human rights violation by 2030. In the context of Malaysia's rate of child marriage, as of October 2010 15, 000 cases were recorded involving teenage girls age below 15 years old (Noor Aziah Mohd Awal & Mohd Al Adib Samuri, 2018). Malaysia has formulated a law called The Law Reform (Marriage & Divorce) Act 1976 which sets the minimum age for marriage at 18 for non-Muslim marriages whereas Islamic Family Laws set the minimum age at 16 for Muslim marriages (Adilah, 2018). Even though there are laws restricted to child marriage, yet Sabah place the third highest child marriage in Malaysia for the year 2013 till 2018 (Mail, 2020). While the total of approved child marriages approved by Jabatan Hal Ehwal Agama Islam Negeri Sabah (JHEINS, 2021) for the year 2015 until the year 2020 was 3779. Out of 3779 cases, the top three causes were Kota Kinabalu with 790 cases (21%), followed by Tawau with 552 cases (14.6%), and Sandakan with 394 cases (10.4%). The balance of 2043 cases were distributed across Sabah districts such as Lahad Datu, Putatan, Papar, and more.